The effects of macroeconomics determinants and secured financing of Islamic Banks on personal insolvency: an empirical investigation on Malaysia - Alias, Zuraina; Azmi, Ruzita; Mohd Yusof, Rosylin (IIUM Press, 2018)
Recent statistics from the Malaysian Department of Insolvency (MDI), and reports from the Malaysian Credit Management Counseling Agency (CMCA) highlight the increasing number of bankrupt borrowers and borrowers registered under the Debt Management Programme (DMP) organized by AKPK. Rising indebtedness can unfavorably influence economic monetary development as it successfully evacuates people from participating or contributing to the economy. Hence, this research is to investigate the issues of personal insolvency in Malaysia and to analyze several macroeconomic determinants, banking variables and Islamic secured financing that affects personal insolvency. The study attempts to inaugurate a long-run cointegration relationship between personal insolvency and independent variables by employing the Auto-Regressive Distributed Lag (ARDL) bounds testing approach and the Vector Autoregression (VAR) model. Based on quarterly data covering the period 2007Q1 to 2016Q4, this study documents evidence of a long-run dynamics with strong bidirectional causality between the house price index and personal insolvency in Malaysia. Accordingly, policies leading to a more efficient housing market while reducing the demand and supply gap affecting house prices will reduce insolvency in Malaysia.